Ninth Five Year Plan 1997-2002 Draft Prepared at the Internal Meetings of the Planning Commission Executive Summary - Planning Commission, Government of India (Planning Commission, Government of India, 1998)
The Ninth Five-Year Plan (1997-2002) of India, framed with a target annual GDP growth of 7%, emphasizes sustainable economic development, social justice, and employment generation. The Plan focuses on enhancing agricultural productivity, ensuring food security, and promoting equitable regional growth, while addressing poverty reduction and empowering marginalized groups. Public sector investments totaling ₹875,000 crore are concentrated on energy, transport, rural development, and agriculture, reflecting the strategic priority sectors. Macroeconomic policies aim to increase domestic savings and investment rates, maintain a manageable current account deficit, and encourage private sector participation alongside public enterprises. Employment opportunities are projected to rise significantly, with total work participation increasing from 389.73 million to 443.62 million, though regional disparities remain, highlighting the need for targeted interventions. The Plan integrates environmental sustainability principles with infrastructural expansion and economic growth. Cooperative federalism, local participation in planning, and robust monitoring mechanisms are emphasized to improve project delivery, transparency, and accountability. Overall, the Ninth Plan seeks to transform India into an inclusive, resilient, and modern economy by balancing growth, social equity, and sustainable development.
Government of India Planning Commission New Delhi
Keywords: Ninth Five Year Plan- India; GDP Growth; Employment Generation; Agriculture; Public Sector Investment; Infrastructure Development; Energy; Rural Development; Regional Disparities